Mephedrone inhalation causes pneumomediastinum. (10th March 2014) - Graham, Ruth; Bowen, Nia; Singh, Joy
Abstract : A 17-year-old male patient presented to A&E with swelling on the right side of his neck, extending to below the clavicle, associated with neck pain and dysphonia. On examination, subcutaneous supraclavicular and chest wall emphysema was noted. Clinical observations and bloods were normal. A chest X-ray and subsequent CT of the thorax showed evidence of pneumomediastinum and subcutaneous emphysema. The patient denied any history of trauma but admitted to inhalation of mephedrone 3 days previously. The patient was discussed with the regional cardiothoracic unit who advised conservative management. He was treated prophylactically with antibiotics and was initially kept nil by mouth, but diet was introduced 24 h later. He remained well, his dysphonia resolved and his subcutaneous emphysema improved. He was discharged after 3 days. He has not attended any formal follow-up but was well when contacted by phone.